Evidence in dentistry guidelines - Macedo, Cristiane Rufino; Atallah, Álvaro Nagib (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Guidelines are suggestions for clinical practice based on the best available scientific evidence. Nevertheless, in drafting such guidelines, existing systematic reviews are often ignored and are replaced by general consensuses. This ends up compromising the quality of the instructions through bias. Our objective was to investigate whether Cochrane systematic reviews were present among the bibliographic references of prevention and treatment guidelines for dentistry that have been published in databases. DESIGN AND SETTING: This retrospective, observational study was conducted at the Brazilian Cochrane Center. Methods: The databases were searched for guidelines. Any guidelines obtained were then checked to find whether Cochrane systematic reviews were present in the bibliographic references of the guidelines. In their absence, we checked whether such reviews had not been included because no reviews existed yet, or because such reviews had not been consulted despite already existing. RESULTS: 223 studies were initially selected; of these, 77 were excluded. Of the 146 guidelines included, 46 could have made reference to existing systematic reviews, but only 13 studies did so. Among these 13 studies, eight were systematic reviews following Cochrane methodology. Thirty-three guidelines had not been drafted using published systematic reviews as references, and 100 guidelines had been unable to use Cochrane references because no reviews existed yet. CONCLUSION: It is necessary to increase awareness of the importance of using systematic reviews in drafting dentistry guidelines. Likewise, it is necessary to develop systematic reviews that answer questions on the various topics that remain unanswered.